2001
DOI: 10.1902/jop.2001.72.11.1535
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Periodontitis by Local Administration of Minocycline Microspheres: A Controlled Trial

Abstract: Scaling and root planing plus minocycline microspheres is more effective than scaling and root planing alone in reducing probing depths in periodontitis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
198
5
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 198 publications
(214 citation statements)
references
References 42 publications
9
198
5
2
Order By: Relevance
“…However, research has focused on the development of a new treatment to appropriately deliver the drug into the periodontal pockets. For instance, a method of microencapsulating minocycline hydrochloride in a bioabsorbable polymer (polyglycolide-co-dl-lactide) has been developed, resulting in microspheres that are administered into sites with periodontal disease 22 . The aim of this study was to evaluate the presence of periodontal pathogens and the clinical response to SRP periodontal pocket treatment associated with subgingival minocycline (SM) in chronic periodontitis subjects.…”
Section: Introductionmentioning
confidence: 99%
“…However, research has focused on the development of a new treatment to appropriately deliver the drug into the periodontal pockets. For instance, a method of microencapsulating minocycline hydrochloride in a bioabsorbable polymer (polyglycolide-co-dl-lactide) has been developed, resulting in microspheres that are administered into sites with periodontal disease 22 . The aim of this study was to evaluate the presence of periodontal pathogens and the clinical response to SRP periodontal pocket treatment associated with subgingival minocycline (SM) in chronic periodontitis subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Quiryen et al suggested that CHX treatment should be re-evaluated as an adjunct to SRP periodontal therapy (Quiryen et al, 2000). While the use of antibiotics (e.g., minocycline and tetracycline) represents a possible adjunct to SRP, and local drug delivery systems can improve clinical and microbial outcomes (Williams et al, 2001), their systemic use has undesirable side effects (e.g., antibiotic resistance, pseudomembranous colitis) (Radvar et al, 1996;Kinane and Radvar, 1999). The development of alternative treatments for periodontitis thus remains an important area of current oral health care research.…”
mentioning
confidence: 99%
“…However, systemic 452 antibiotics should not be used in treatment of all forms of chronic periodontitis (13) , the development of resistance as well as drug interactions as a side effects are important reasons to limit the usage of systemic chemotherapeutic agents and to begin a new era in usage of topical sub-gingival delivery of therapeutic agents (14) .The main advantage of the topical delivery system therapy is to bring high concentrations and slowly sustained release of chemotherapeutic agents within the periodontal pocket without exposing the whole body to avoid their systemic side effects (15) . For example, the local delivery systems of chlorhexidine in a bio-absorbable chips for sustained release, this added benefits to SRP (16,17) .Another similar improvements were observed with adjunctive use of locally administrated microencapsulated tetracycline as minocycline (18,19) .…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 70%